Ответы и объяснения

2013-06-18T19:11:12+04:00

2.

1) (a-b)/(2a-b)-(a^2+a+b^2)/(2a^2+ab-b^2)=(a-b)/(2a-b)-(a^2+a+b^2)/((a^2+ab)+(a^2-b^2))=(a-b)/(2a-b)-(a^2+a+b^2)/(a(a+b)+(a-b)(a+b))=(a-b)/(2a-b)-(a^2+a+b^2)/(a+b)/(2a-b)=(a-b)(a+b)/(2a-b)/(a+b)-(a^2+a+b^2)/(a+b)/(2a-b)=((a^2-b^2-a^2+a-b^2))/(a+b)/(2a-b)=-(2b^2+a)/(a+b)/(2a-b)

2) (4b^4+4ab^2+a^2)/(2b^2+a)=(a+2b^2)^2/(2b^2+a)=2b^2+a

3) (b^2+b+ab+a)*(-(2b^2+a)/(a+b)/(2a-b))/(2b^2+a)=-(b(b+1)+a(b+1))*(2b^2+a)/(a+b)/(2a-b)/(2b^2+a)=-(b+1)(a+b)(2b^2+a)/(a+b)/(2a-b)/(2b^2+a)=-(b+1)/(2a-b)=(b+1)/(-2a+b)=